Törvények, kompetenciák, kérdések – a felnőttoktatás válsá-gának korrajza a XXI. század első harmadából - Nógrádiné Pócs, Lujza; Gyöngyösiné Szabó, Judit (Acta Scientiarum Socialium, 2014)
Regulations, competences, questions – crisis in adult education in the first third of the 21st century In my thesis I am investigating the causes of the crisis in the first third of the 21st century in primary and secondary level adult education from two aspects. Both the objective, bureaucratic and legislative factors, as well as the intrinsic motivational basis with the family background and net of competencies will be taken into account. All of these factors are significant in enabling the individuals to complete their secondary studies during their adult years so that they are able to hold positions that require higher qualifications and, thus, improve their chances of making a living. When analysing competencies, teacher competencies are also taken into consideration to relate to the quality control programme of teachers within the new teacher career model. Further, the findings of a questionnaire that was filled in by my fellow teachers taking part in the public work programme are analysed and evaluated. I look at the negative impact of the changes in the education policy to include unem-ployment, migration, dropping out, issues with career orientation, the lack of follow-up on those entering the job market, as well as the solutions offered by the education policy: the BRIDGE and the public work programmes, both of which aim at assisting the unskilled in catching up. Finally I make an attempt to suggest feasible solutions to the problems above and highlight the competencies, which are required for successful physical and mental achievement. As a conclusion, I emphasize the importance of sustaining the adult education system in order to improve chances for life-long learning in Hungary.
Keywords: adult education; life-long learning; educational policy; motivational factors; competencies; teacher career model